Metabolomic analysis and identification of a role for the orphan human cytochrome P450 2W1 in selective oxidation of lysophospholipids[S] - Yi Xiao; 肖毅; F. Peter Guengerich (Journal of Lipid Research, 2012)
Human cytochrome P450 (P450) 2W1 is still considered an “orphan” because its physiological function is not characterized. To identify its substrate specificity, the purified recombinant enzyme was incubated with colorectal cancer extracts for untargeted substrate searches using an LC/MS-based metabolomic and isotopic labeling approach. In addition to previously reported fatty acids, oleyl (18:1) lysophosphatidylcholine (LPC, lysolecithin) was identified as a substrate for P450 2W1. Other human P450 enzymes tested showed little activity with 18:1 LPC. In addition to the LPCs, P450 2W1 acted on a series of other lysophospholipids, including lysophosphatidylinositol, lysophosphatidylserine, lysophosphatidylglycerol, lysophosphatidylethanolamine, and lysophosphatidic acid but not diacylphospholipids. P450 2W1 utilized sn-1 18:1 LPC as a substrate much more efficiently than the sn-2 isomer; we conclude that the sn-1 isomers of lysophospholipids are preferred substrates. Chiral analysis was performed on the 18:1 epoxidation products and showed enantio-selectivity for formation of (9R,10S) over (9S,10R). The kinetics and position specificities of P450 2W1-catalyzed oxygenation of lysophospholipids (16:0 LPC and 18:1 LPC) and fatty acids (C16:0 and C18:1) were also determined. Epoxidation and hydroxylation of 18:1 LPC are considerably more efficient than for the C18:1 free fatty acid.